Diabetes Mellitus and Drug Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Three teenagers with well-controlled epilepsy who developed drug refractory partial seizures correlated with nonketotic hyperglycemia and insulin-dependent diabetes mellitus are reported from the Children's Hospital of Eastern Ontario, University of Ottawa, and Children's Hospital, Dalhousie University, Halifax, Nova Scotia, Canada.